2000
DOI: 10.1207/s15328015tlm1204_8
|View full text |Cite
|
Sign up to set email alerts
|

The Program for Professional Values and Ethics in Medical Education

Abstract: PPVEME is an attempt to construct a medical school learning environment around professionalism. Evaluation over time will tell how successfully that has been accomplished.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0
1

Year Published

2002
2002
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 8 publications
1
19
0
1
Order By: Relevance
“…Previous research suggested that positive attitudes of residents toward ethics preparation improved beneficial outcomes of educational innovations [8]. Such findings support the belief that assessing trainees' attitudes, views and preferences is important in developing curricular approaches attuned to their concerns and experiences [9]. This information may help in the creation of curricular content and methods that are more acceptable to trainees [10,11].…”
Section: Discussionsupporting
confidence: 54%
“…Previous research suggested that positive attitudes of residents toward ethics preparation improved beneficial outcomes of educational innovations [8]. Such findings support the belief that assessing trainees' attitudes, views and preferences is important in developing curricular approaches attuned to their concerns and experiences [9]. This information may help in the creation of curricular content and methods that are more acceptable to trainees [10,11].…”
Section: Discussionsupporting
confidence: 54%
“…2 Reports on course development and effectiveness appear regularly in mainstream journals. [3][4][5][6][7] A 1998 survey of all 125 American medical schools discovered that almost 90% of the 116 respondents included some formal instruction in professionalism. 8 Although professionalism and humanism are not synonymous, those who advocate for either or both are generally motivated by similar concerns.…”
mentioning
confidence: 99%
“…Large group movie-excerpt viewing with limited discussion or participation in a study in Tulane University was shown to be ineffective while small-group discussions and role-plays were effective. Generally, the teaching strategies chosen played important roles in effective learning (Lazarus et al, 2000).…”
Section: Discussionmentioning
confidence: 99%